2014
DOI: 10.1093/humrep/deu273
|View full text |Cite
|
Sign up to set email alerts
|

First trimester trophoblast and placental bed vascular volume measurements in IVF or IVF/ICSI pregnancies

Abstract: This study was financially supported by the Erasmus Trustfonds, the Meindert de Hoop foundation and the Fonds NutsOhra. No competing interests are declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…(30) As these diseases of placental alterations have been shown to have detectably smaller placental volumes on first trimester ultrasound, only one small study investigated whether there is a difference in placental volume in IVF conceptions compared to spontaneous conceptions, finding no difference, but it was limited to sample size. (17) We also did not find a difference in placental size based on volume and chorionic villi obtained at CVS comparing pregnancies from couples with infertility to spontaneous conceptions nor did we find differences among the fertility treatments (NIFT versus IVF). Our study was significantly larger and was adequately powered to detect a clinically significant difference in EPV that has been associated with fetal growth restriction, an outcome noted in gestations conceived with fertility treatments.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…(30) As these diseases of placental alterations have been shown to have detectably smaller placental volumes on first trimester ultrasound, only one small study investigated whether there is a difference in placental volume in IVF conceptions compared to spontaneous conceptions, finding no difference, but it was limited to sample size. (17) We also did not find a difference in placental size based on volume and chorionic villi obtained at CVS comparing pregnancies from couples with infertility to spontaneous conceptions nor did we find differences among the fertility treatments (NIFT versus IVF). Our study was significantly larger and was adequately powered to detect a clinically significant difference in EPV that has been associated with fetal growth restriction, an outcome noted in gestations conceived with fertility treatments.…”
Section: Discussionmentioning
confidence: 55%
“…(1216) Thus, placental volume may be a marker of placental insufficiency in early gestation. To date, there has only been one small study comparing 1 st trimester placental volume based on mode of conception and while these authors found no differences in 10 week placental volumes between 84 pregnancies conceived spontaneously compared to 70 pregnancies conceived by IVF, this was largely limited by small sample size (17). In addition, these investigators did not address NIFT conceptions which are also associated with increased risk of pregnancy related complications (6)…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rifouna et al analyzed 70 IVF pregnancies and found no difference with respect to control pregnancies in placental vascular volume at 12 weeks and trophoblastic volume at 10 weeks of gestation. The difference in the technique used to evaluate the placenta and the difference in the characteristics of IVF pregnancies (oocyte donation occurred only in two cases) and in the sample size analyzed (70 vs 416 in the present study) may explain the differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that IVF pregnancies have an increased risk of placenta previa and placenta abruption (27), as well as a higher incidence of marginal cord insertion and abnormal placental shapes (28). Small studies on first trimester trophoblast and placental bed vascular volume as an indicator of normal placentation did not show a difference between IVF and spontaneous conceptions (29). Frozen embryo transfers may create an environment more prone to abnormal placentation, which in turn translates to the higher risk of biochemical pregnancy and pregnancy loss observed in this study.…”
Section: Discussionmentioning
confidence: 88%